Response of Pigeonpea (Cajanus cajan) varieties to organic manures and their influence on fertility and enzyme activity of soil* - RAMESH, P; SINGH, MOHAN; PANWAR, N R; SINGH, A B; RAMANA, S (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during the rainy seasons of 2003 and 2004 to study the effect of 6 nutrient sources (chenmcal fertilizers@30 kgN+26.2 kg Plha, 3 tonnes/ ha vennicompost, 3 tonnes/ha phosphocompost, 2 tonnes/ ha poultry manure, 4 tonnes/ha cattle dung manure and control) on the growth, yield and protein content of 4 pigeonpea [Cajanus cajan (L.) Millsp] varieties (’ICPL 87119’, ’Jowahar 4’, ’BDN 2’ and ’Aasha’) and their influence on fertility and enzyme activity of soil. Among the varieties ’ICPL 87119’ recorded higher plant height, branches/plant, biomass accumulation, pods/plant, IOO-seed weight and higher seed and straw yield whereas, ’BDN 2’ recorded the lowest growth and yield but higher protein content. Application of cattle dung manure and chemical fertilizers recorded similar growth, yield attributes, protein’ content and seed yield whereas application of vermicompost and phosphoeompost resulted in identical growth, yield attributes and yield. Poultry manure application recorded the ’lowest crop growth and yield. Application of cattle dung manure resulted in higher soil organic carbon, available Nand K and increased the dehydrogenase and phosphatase activity of soil compared to chemical fertilizers and control.